Mengungkap Tanda-tanda Skandal Korupsi 271 T PT Timah Tbk, Analisis Earning Opacity - Saputri, Novia Linda; Irene, Keren Freti (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2024)
This study aims to uncover the early signs of a Rp 271 trillion corruption scandal at PT Timah Tbk through Earning Opacity analysis. Earning Opacity refers to the lack of clarity in financial statements that hinders external parties from comprehending the company’s financial condition transparently. In this case, financial statement manipulation is suspected to conceal illegal activities that harm various stakeholders, including investors and the public. This research employs secondary data from PT Timah Tbk's annual financial reports between 2019 and 2023. Through descriptive analysis and statistical tests, strong indications of earnings manipulation were found, such as abnormal fluctuations in revenue, operating cash flow, and Dividends Per Share (DPS). The analysis also shows a significant relationship between Earning Opacity and indications of the corruption scandal, supported by discrepancies between the company's income statement and cash flow statement. These findings emphasize the importance of transparency and accountability in financial reporting to prevent corruption practices in state-owned enterprises. Furthermore, the study provides recommendations to enhance internal and external oversight and reduce opportunities for financial statement manipulation through stricter regulations. This research is expected to serve as a reference for identifying corruption risks in the future.